2014
DOI: 10.1371/journal.pone.0085902
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Expression Analysis Suggests Perturbation of Vascular Homeostasis during High Altitude Pulmonary Edema

Abstract: BackgroundHigh altitude pulmonary edema (HAPE) is a life-threatening form of non-cardiogenic edema which occurs in unacclimatized but otherwise normal individuals within two to four days after rapid ascent to altitude beyond 3000 m. The precise pathoetiology and inciting mechanisms regulating HAPE remain unclear.Methodology/Principle findingsWe performed global gene expression profiling in individuals with established HAPE compared to acclimatized individuals. Our data suggests concurrent modulation of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…It contributes to HIF-2A stability and regulation. EGLN-3 inhibits HIF-2α modulated hypoxia responsive elements [34]. As evident from previous studies that mitochondria plays a role in HAPE susceptibility the mitochondrial haplotype has also been found associated with susceptibility.…”
Section: A) Polymorphism In Genes Involved In Hypoxia Signalingmentioning
confidence: 69%
See 3 more Smart Citations
“…It contributes to HIF-2A stability and regulation. EGLN-3 inhibits HIF-2α modulated hypoxia responsive elements [34]. As evident from previous studies that mitochondria plays a role in HAPE susceptibility the mitochondrial haplotype has also been found associated with susceptibility.…”
Section: A) Polymorphism In Genes Involved In Hypoxia Signalingmentioning
confidence: 69%
“…Recently a study at by Sharma et al [34] showed differential expression of a large clad of genes associated with energy metabolism were altered during hypoxia and may therefore be associated to the susceptibility. Genome wide profiling associated differential regulation of OXPHOS (oxidative phosphorylation) pathways to HAPEsusceptibility.…”
Section: Evidences From Genomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leukocytic invasion into other ischemic or hypoxic tissues has also been reported [50,51,52,53,54,55,56,57]. However, the triggers for these specific inflammatory responses of the pulmonary vascular system are still unidentified [58,59,60,61]. Recent progress on this issue will be discussed further.…”
Section: Alveolar Hypoxia Evokes Specific Pulmonary Responsesmentioning
confidence: 99%